Understanding barriers to decision making in the UK energy-food-water nexus: The added value of interdisciplinary approaches. Issue 61 (July 2016) - Howarth, Candice; Monasterolo, Irene
Highlights: Transdisciplinary approaches can better inform decision making in the context of nexus shocks. Cross-sectoral, innovative, reflective perspectives better assess impacts and implications of climate shocks across the nexus. We identify and discuss barriers to sectoral responses to nexus shocks in the UK. Cross-sectoral, multi-disciplinary participatory processes enhance knowledge co-production. Inter-disciplinary approaches to nexus shocks are complex due to social and practical limitations. Abstract: The nexus represents a multi-dimensional means of scientific enquiry which seeks to describe the complex and non-linear interactions between water, energy, food, with the climate, and further understand wider implications for society. These resources are fundamental for human life but are negatively affected by shocks such as climate change and characterize some of the main challenges for global sustainable development. Given the multidimensional and complex nature of the nexus, a transdisciplinary approach to knowledge development through co-production is needed to timely and effectively inform the decision making processes to build societal resilience to these shocks going beyond the sectorality of current research practice. The paper presents findings from five themed workshops (shocks and hazards, infrastructure, local economy, governance and governments, finance and insurance) with 80 stakeholders from academia, government and industry in the UK to explore the impact of climate and weather shocks across the energy-food-water nexus and barriers to related responses. The research identified key stakeholders' concerns, opportunities and barriers to better inform decision making centred on four themes: communication and collaboration, decision making processes, social and cultural dimensions, and the nature of responses to nexus shocks. We discuss implications of these barriers and how addressing these can better facilitate constructive dialogue and more efficient decision-making in response to nexus shocks.